A descriptive study on the roles of fathers as manifested in the utilization of infant spaces among selected middle-class Filipino households - Lanting, Christine Joy D.; Faustino, Johanna Victoria A. (Quezon City College of Home Economics, University of the Philippines Diliman, 2017)
The purpose of this study was to determine the main infant space in the Filipino households and how this space is utilized to accommodate the roles of the fathers in childrearing. Participants of this study included six (6) selected fathers of middle-class Filipino families in Metro Manila with both parents living under the same roof, earning a living, and having a child age two (2) years and below. It was assumed that the roles of the fathers in child-rearing affected the utilization of infant spaces and this relationship is influenced by proxemics theory which relates culture in the use of space and the socio-economic status of the family. The study is a qualitative-descriptive research which used non-probability sampling, particularly purposive sampling. Data was gathered through observation, interviews, and photo documentation of existing infant spaces. The findings of the study were generated through thematic analysis. The results of the study revealed that the infant space commonly used by the selected middle-class Filipino families is either the living area or the bedroom. Playing and changing of clothes or diapers were the most common activities done by the selected fathers in this space. Infant furniture pieces and accessories that were used by the father were also identified. Improvements regarding safety and additional space were highlighted by the fathers as aspects that would help fully accommodate their child-rearing activities. In conclusion, although the furniture pieces and accessories were removed, added, moved or redefined in the living area and bedroom to cater to the activities done by the father in child-rearing such as playing and changing of diapers, these changes are still not enough to fully accommodate their child-rearing activities. Safety and a wide space that can facilitate different kinds of play should also be taken into consideration.
submitted June 2017
Thesis (B.S. Interior Design)--University of the Philippines Diliman.
Keywords: Nurseries -- Decoration -- Philippines; Father and child -- Philippines